Comparison of analytical film theory and a numerical model for predicting concentration polarisation in membrane gas separation - K., Foo; Y. Y., Liang; P. S., Goh; A. L., Ahmad; D. K., Wang; D. F., Fletcher (Elsevier Ltd, 2022)
Accurate prediction of the concentration polarisation (CP) effect is very important in the design of an efficient membrane-based gas separation process. This study analyses the reliability of analytical film theory (FT) for evaluating the performance of gas separation membranes in terms of CP and flux. The analytical model is compared against a more rigorous numerical model developed by using Computational Fluid Dynamics (CFD) for various operating variables. The results show that the FT prediction is less accurate at high CP conditions when gas permeation through the membrane increases, due to higher permeance selectivity and pressure ratio. Hence, the results suggest that FT is not recommended for membranes with high permeance or high-pressure conditions. Given that the typical range of feed composition and temperature has little impact on fluid properties (i.e., gas diffusion coefficient, densities, and viscosities), the resulting CP does not vary much and hence both FT and CFD models predict a similar CP. The analysis also suggests that the FT model is more accurate in predicting CP in the region closer to the membrane entrance. Overall, the analytical film theory serves as a reliable approximation in membrane gas applications under low CP at high crossflow and low flux conditions.